2014
DOI: 10.1016/j.hjdsi.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A potential new data source for assessing the impacts of health reform: Evaluating the Gallup-Healthways Well-Being Index

Abstract: Background: Existing national health-related surveys take several months or years to become available. The Affordable Care Act will bring rapid changes to the health care system in 2014. We analyzed the Gallup-Healthways' Well-Being Index (WBI) in order to assess its ability to provide real-time estimates of the impact of the ACA on key health-related outcomes. Methods:We compared the Gallup-Healthways WBI to established surveys on demographics, health insurance, access to care, and health. Data sources were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
(9 reference statements)
1
28
0
Order By: Relevance
“…32,33 The income information in the WBI is limited, which means that our estimates of income as a percentage of poverty are imprecise, and previous research has shown that the survey overrepresents the middle of the income distribution. 8 Nonetheless, we found logical patterns of coverage on the basis of these measurements, and results were similar when we excluded observations with missing income data.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…32,33 The income information in the WBI is limited, which means that our estimates of income as a percentage of poverty are imprecise, and previous research has shown that the survey overrepresents the middle of the income distribution. 8 Nonetheless, we found logical patterns of coverage on the basis of these measurements, and results were similar when we excluded observations with missing income data.…”
Section: Discussionsupporting
confidence: 56%
“…The WBI has been validated for these measures, but it less reliably distinguishes between different types of coverage (e.g., Medicaid vs. private insurance). 8 We used multivariate regression to model the likelihood of each outcome over time. The primary analysis modeled a linear monthly time trend, with sensitivity analyses that either added a quadratic time trend or did not include a time trend.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations